2018
DOI: 10.1111/ajt.14498
|View full text |Cite
|
Sign up to set email alerts
|

Taking the challenge: A protocolized approach to optimize Pneumocystis pneumonia prophylaxis in renal transplant recipients

Abstract: While trimethoprim-sulfamethoxazole is considered first-line therapy for Pneumocystis pneumonia prevention in renal transplant recipients, reported adverse drug reactions may limit use and increase reliance on costly and less effective alternatives, often aerosolized pentamidine. We report our experience implementing a protocolized approach to trimethoprim-sulfamethoxazole adverse drug reaction assessment and rechallenge to optimize prophylaxis in this patient cohort. We retrospectively reviewed 119 patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Urbancic et al reported on a TMP‐SMX re‐challenge protocol in kidney transplant recipients; nearly three quarters (74% of 27 patients) tolerated protocol‐driven re‐challenge without allergic or adverse drug reaction resulting in discontinuation, supporting previous literature that an initial non‐severe, non‐anaphylactic sulfonamide reaction does not preclude subsequent tolerance . McLaughlin et al reported on switch to atovaquone and subsequent successful re‐initiation of TMP‐SMX in 100% (n = 14) of kidney transplant recipients who were re‐challenged; in this retrospective review, however, all but one of the 14 patients who were re‐challenged with TMP‐SMX had been switched to atovaquone for reasons other than hypersensitivity (eg, neutropenia, hyperkalemia, renal insufficiency).…”
Section: Discussionmentioning
confidence: 73%
“…Urbancic et al reported on a TMP‐SMX re‐challenge protocol in kidney transplant recipients; nearly three quarters (74% of 27 patients) tolerated protocol‐driven re‐challenge without allergic or adverse drug reaction resulting in discontinuation, supporting previous literature that an initial non‐severe, non‐anaphylactic sulfonamide reaction does not preclude subsequent tolerance . McLaughlin et al reported on switch to atovaquone and subsequent successful re‐initiation of TMP‐SMX in 100% (n = 14) of kidney transplant recipients who were re‐challenged; in this retrospective review, however, all but one of the 14 patients who were re‐challenged with TMP‐SMX had been switched to atovaquone for reasons other than hypersensitivity (eg, neutropenia, hyperkalemia, renal insufficiency).…”
Section: Discussionmentioning
confidence: 73%
“…19 Therefore, for those with mild delayed TMP-SMX allergy, TMP-SMX rechallenge or desensitization should be considered in the peritransplant period or at commencement of induction chemotherapy, as an alternative to dapsone in accordance with previously published protocols. 9 This study highlights that although dapsone is an alternative agent in PJP prophylaxis, it requires careful monitoring of oxidative…”
Section: Discussionmentioning
confidence: 94%
“…A recent Cochrane review of PJP prophylaxis in the non‐HIV setting found no difference in adverse events requiring discontinuation when comparing TMP‐SMX to no treatment or placebo . Therefore, for those with mild delayed TMP‐SMX allergy, TMP‐SMX rechallenge or desensitization should be considered in the peritransplant period or at commencement of induction chemotherapy, as an alternative to dapsone in accordance with previously published protocols …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…TMP is usually used in combinationwith Sulfamethoxazole (SMX) to treat lower urinary tract infections and acute invasive diarrhea/bacterial dysentery as first and second choice, respectively (WHO, 2017), respiratory infections in cystic fibrosis patients caused by Staphylococcus aureus , among other many infections. Lately, it has also been used for preventing infections from the opportunistic pathogen Pneumocystis carinii (Urbancic et al, 2018), which normally causes pneumonia in patients with AIDS. Both drugs act on the folic acid biosynthetic route by inhibiting two enzymes: dihydrofolate reductase (DHFR) and dihydropteroate synthetase, respectively.…”
Section: Introductionmentioning
confidence: 99%